Effect of impurity content on structure of living water - Hao Shiming; Li Haisheng; Li Xinzhong; Li Liben; Xie Jingpei (Химия и технология воды, 2016)
In order to study the influence of impurities content on the water structure, Raman spectra and degrees of depolarization of different living water are measured by Raman spectroscopy, the relationship between the depolarization ratio and the impurity content in drinking water was obtained by the utilisation of computer deconvolution for the stretching vibration peak. The results showed that the intensity of different bending vibration is almost the same, and the intensity of the stretching vibration reflects different content of impurities in water. Depolarization calculation of water molecules showed that the stretching vibration is stronger than the bending vibration. The interaction of impurity ions and water molecules enhances the vibration rate of water molecules, making the symmetry of stretching vibration reduced, and leading to increased depolarization ratio. Therefore, the impurities content can be determined from the relative intensity of Raman characteristic peaks and the degrees of depolarization